2016
DOI: 10.1523/jneurosci.0006-16.2016
|View full text |Cite
|
Sign up to set email alerts
|

Insulin-Independent GABAAReceptor-Mediated Response in the Barrel Cortex of Mice with Impaired Met Activity

Abstract: Autism spectrum disorder (ASD) is a neurodevelopmental disorder caused by genetic variants, susceptibility alleles, and environmental perturbations. The autism associated gene MET tyrosine kinase has been implicated in many behavioral domains and endophenotypes of autism, including abnormal neural signaling in human sensory cortex. We investigated somatosensory thalamocortical synaptic communication in mice deficient in Met activity in cortical excitatory neurons to gain insights into aberrant somatosensation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
16
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(20 citation statements)
references
References 49 publications
4
16
0
Order By: Relevance
“…In animals, unlike humans, IPSCs produced through GABA receptors may be observed using whole-cell recording techniques [ 61 , 62 ]. For example, Lo et al [ 63 ] showed markedly reduced GABA A -mediated IPCSs in the barrel cortex of ASD model mice, confirming deficits in the GABA system. However, in vivo recordings of IPSPs are challenging and, to the best of our knowledge, this has not yet been conducted on ASD model animals.…”
Section: Discussionmentioning
confidence: 99%
“…In animals, unlike humans, IPSCs produced through GABA receptors may be observed using whole-cell recording techniques [ 61 , 62 ]. For example, Lo et al [ 63 ] showed markedly reduced GABA A -mediated IPCSs in the barrel cortex of ASD model mice, confirming deficits in the GABA system. However, in vivo recordings of IPSPs are challenging and, to the best of our knowledge, this has not yet been conducted on ASD model animals.…”
Section: Discussionmentioning
confidence: 99%
“…Human imaging and genetic studies have identified mutations in the MET gene as a risk factor for autism spectrum disorder (ASD; Peng et al, 2013), but the exact role of MET in ASD is not yet understood (Eagleson et al, 2017). Previous studies in neurons have implicated MET in regulating postsynaptic strength in excitatory neurons (Qiu et al, 2014;Lo et al, 2016), excitatory synapse formation (Xie et al, 2016), and interneuron migration (Martins et al, 2011). We found that reducing MET levels specifically in inhibitory axons blocked Sema4D-induced inhibitory bouton stabilization, suggesting that presynaptic MET acts as a coreceptor with PlexinB1 (or other family members; McDermott et al, 2018) to mediate actin remodeling in the presynaptic bouton.…”
Section: Discussionmentioning
confidence: 99%
“…Consistent with this scenario, we found that MET is336 enriched in a subset of inhibitory synapses, both in primary hippocampal cultures and 337 organotypic slices. Previous studies have implicated MET in regulating postsynaptic strength338 in excitatory neurons(Lo et al, 2016, Qiu et al, 2014, and in interneuron migration during339 early stages of neuronal development(Martins et al, 2011). Our data indicate a novel role340 for MET in the assembly of inhibitory presynapses.341 342 Our observation that Sema4D-induced bouton stabilization requires ongoing neuronal343 activity suggests that this process plays a role during activity-dependent inhibitory plasticity.344 A number of recent papers have described a rapid response of inhibitory axons to changes in345 activity levels(Schuemann et al, 2013) and GABA B signaling(Fu et al, 2012) in vitro, as well346 as to sensory deprivation(Keck et al, 2011) and motor learning(Chen et al, 2015) in vivo.347 The fast inhibitory response may serve as a gating mechanism for plasticity at nearby 348 excitatory synapses, which takes place at a slower time scale(Froemke, 2015, Froemke et al, 349 2007, Hensch, 2005, Keck et al, 2011, Villa et al, 2016).…”
mentioning
confidence: 99%